2009
DOI: 10.1111/j.1551-2916.2009.03298.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Dielectric‐Permittivity Phenomena of Compositionally and Structurally CaCu3Ti4O12‐Like Oxide Ceramics

Abstract: SrCu3Ti4O12, La2/3Cu3Ti4O12, and Bi2/3Cu3Ti4O12 ceramics were representatively investigated to obtain a systematical understanding about the dielectric behaviors of the compositionally and structurally CaCu3Ti4O12‐like oxides and the underlying related mechanism. In opposite to the literature results, giant dielectric‐permittivity phenomena with low‐frequency ɛ′ larger than 1.5 × 104 have been observed in all of these ceramics. Furthermore, the existence of CuO secondary phase has been confirmed in them. In ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…The high frequency and low temperature response is related to semiconducting grains and that predominant at low frequencies and high temperatures is attributed to insulating grain boundaries [8][9][10][11]. In the dielectric permittivity versus frequency plots there are two plateaus -a very high reaching 10 5 at low frequencies which originates from internal barrier layer capacitance effects and a low one at a level of 200 which occurs at high frequencies and is related to intrinsic properties of the material [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high frequency and low temperature response is related to semiconducting grains and that predominant at low frequencies and high temperatures is attributed to insulating grain boundaries [8][9][10][11]. In the dielectric permittivity versus frequency plots there are two plateaus -a very high reaching 10 5 at low frequencies which originates from internal barrier layer capacitance effects and a low one at a level of 200 which occurs at high frequencies and is related to intrinsic properties of the material [9].…”
Section: Resultsmentioning
confidence: 99%
“…Lead-free nonferroelectric high dielectric constant materials with perovskite structure and ACu 3 Ti 4 O 12 composition (A = Ca, Bi 2/3 , Y 2/3 , La 2/3 , Nd 2/3 , Sm 2/3 , Gd 2/3 , Dy 2/3 ) [6][7][8][9][10][11][12] could be promising candidates to replace relaxors as dielectrics in MLCCs. These compounds exhibit relatively low sintering temperature enabling co-firing with Ag electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the complete ion-substitution compounds ACu 3 Ti 4 O 12 (A = Cd, Sr, La 2/3 , Y 2/3 , Bi 2/3 , Na 1/2 Bi 1/2 etc.) all exhibit the same giant dielectric constant and perovskite-like crystal structure as CaCu 3 Ti 4 O 12 with space group Im 3 [25][26][27][28][29][30]. However, Subramanian et al [1] pointed out in 2000 that the dielectric constant of CaCu 3 Ti 4 O 12 measured at 100 kHz and room temperature was more than five times larger than other kinds of ACu 3 Ti 4 O 12 compounds.…”
Section: Introductionmentioning
confidence: 96%
“…Besides CCTO ceramics, there are several reports on the giant ε properties of CCTO-related materials, i.e., ACu 3 Ti 4 O 12 phases where A = Sr, Cd, Bi 2/3 , La 2/3 , Y 2/3 , Na 1/2 Bi 1/2 , and the rare earths [16][17][18][19][20][21][22][23]. Hao et al [24] found that NaCu 3 Ti 3 SbO 12 , having a perovskite-related crystallographic structure, can exhibit a giant value of ε (∼10 4 below 100 kHz).…”
Section: Introductionmentioning
confidence: 99%